Global status of lignocellulosic biorefinery: Challenges and perspectives. (January 2022) - Singh, Nisha; Singhania, Reeta Rani; Nigam, Poonam S.; Dong, Cheng-Di; Patel, Anil Kumar; Puri, Munish
Graphical abstract: Highlights: Lignocellulosic (LC) biorefinery is gaining global attention for better feasibility. LC bioethanol can be integrated with high value biochemicals productions. Advances in tailor-made enzyme cocktails and pretreatments offer brighter scope. LC biorefinery is being mandatory for better carbon footprints and energy balance. LC biorefinery exhibit sustainable features for global circular bioeconomy. Abstract: The bioprocessing of lignocellulosic biomass to produce bio-based products under biorefinery setup is gaining global attention. The economic viability of this biorefinery would be inclined by the efficient bioconversion of all three major constituents of lignocellulosic biomass i.e. cellulose, hemicellulose, and lignin for value-added biochemicals and biofuels production. Although the lignocellulosic biorefinery setup has a clear value proposition, the commercial success at the industrial scale is still inadequate. This can be attributed mainly to irregular biomass supply chain, market uncertainties, and scale-up challenges. Global research efforts are underway by public and private sectors to get deeper market penetration. A comprehensive account of important factors, limitations, and propositions are worth consideration for the commercial success of lignocellulosic biorefineries. In this article, the importance of integration of lignocellulosic biorefineries with existing petrochemical refineries, the technical challenges of industrialization, SWOT analysis, and future directions have been reviewed.